Current Aspects of Disability in the Kyrgyz Republic - Mamatov Sagynali Murzaevich1 , Tolkunbek Baimuratov2 , Ulan Aliev2 , Ziyabidin Aidarov3 , Chyngyzbek (Indian Journal of Forensic Medicine & Toxicology, 2020)
The objective is to study the epidemiological characteristics and assess the system for establishing a disability in the Kyrgyz Republic. In establishing disability, a biomedical model of health is used, which does not provide an objective assessment of a person’s condition. This study analyzes data on the disability situation in the Kyrgyz Republic, which indicates a steady annual increase in the disability rate. For children under 18 years of age, the establishment of disability and assignment of the category “disabled child” is biased, since only the state of health and dysfunction of the child’s functional abilities are assessed and, despite the difference in the severity of the condition, the possibility of work capacity and the ability to participate in education is not evaluated.